2001
DOI: 10.1029/2000jb900325
|View full text |Cite
|
Sign up to set email alerts
|

Rheological evolution during extension at nonvolcanic rifted margins: Onset of serpentinization and development of detachments leading to continental breakup

Abstract: Abstract. Within the continent-ocean transition several nonvolcanic rifted margins exhibit a zone of partially serpentinized peridotites which continue under the thinned and faulted continental crust and are thought to represent subcontinental lithosphere serpentinized by contact with water. As water in sufficient volumes can only come from the surface, we suggest that a major condition for the onset of serpentinization is the embrittlement of the entire crust during progressive extension and hence the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
215
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(240 citation statements)
references
References 55 publications
18
215
1
Order By: Relevance
“…As the margin extended and thinned at an ultra-slow rate (< 10 mm/yr half spreading rate), it allowed time for the entire crust to cool conductively, resulting in the normally ductile midand lower-crust becoming progressively embrittled (Srivastava et al 2000;Pérez-Gussinyé and Reston 2001;Pérez-Gussinyé et al 2003). Once the crustal thicknesses reached < 10 km, the entire crust became brittle and coupled, a phenomenon known as continental hyperextension.…”
Section: Geologic Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…As the margin extended and thinned at an ultra-slow rate (< 10 mm/yr half spreading rate), it allowed time for the entire crust to cool conductively, resulting in the normally ductile midand lower-crust becoming progressively embrittled (Srivastava et al 2000;Pérez-Gussinyé and Reston 2001;Pérez-Gussinyé et al 2003). Once the crustal thicknesses reached < 10 km, the entire crust became brittle and coupled, a phenomenon known as continental hyperextension.…”
Section: Geologic Settingmentioning
confidence: 99%
“…A fully embrittled crust enabled normal faults to form through the entire crust, from the seafloor to the underlying mantle (Pérez-Gussinyé and Reston 2001;Pérez-Gussinyé et al 2003;Pérez-Gussinyé 2013). These faults acted as conduits, delivering seawater to the upper mantle and forming a layer of serpentinised mantle, which is an inherently weak material (Pérez-Gussinyé and Reston 2001;Reston et al 2007;. With continued extension these faults soled out into the structurally weak layer of mantle serpentinite, forming a large and low angle (< 20⁰) detachment fault, known as the S-reflector (Fig.…”
Section: Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditions that favour embrittlement are slow extension and low sedimentation rates (a sedimentary layer can have a 'blanketing' effect, increasing temperatures in the underlying crust). Pérez-Gussinyé & Reston (2001) found that stretching factors of between about 3 and 5 were required for embrittlement to occur, depending on the strain rate. The simulations of Rüpke et al (2013) produced similar results when there was no sedimentation, but demonstrated that higher factors were required when the sediment supply was increased.…”
Section: Hyperextension Is a Deformation Mode Affectingmentioning
confidence: 99%
“…We neglect the effects of water migration because of the expected very high water velocities compared with the chosen time steps and total computational time (Quinquis & Buiter 2014); thus, hydration can be considered instantaneous in our model. The latent heat of serpentinization is also neglected because it is balanced by the latent heat produced by de-serpentinization and melting at large scales (Pérez-Gussinyé & Reston 2001;Rupke et al, 2004Rupke et al, , 2013. Furthermore, it has been suggested that a latent heat of serpentinization of 2.9 × 10 5 J kg −1 (Emmanuel & Berkowitz 2006) results in an increase in temperature of 300 • C (Rupke et al 2013); therefore, the serpentine would cease to be stable.…”
Section: Introductionmentioning
confidence: 99%